Cutaneous Eccrine Adenolipoma with a Spindle Cell Component. (28th October 2020) - Karimi, S S; Braniecki, M; Bain, M; Jetter, N; Murray, T
Abstract: Introduction/Objective: Cutaneous adenolipoma is a rare, benign variant of solitary lipoma characterized by a mature adipocytic proliferation with entrapped eccrine or apocrine sweat glands. It is found predominately in middle-aged females, with a predilection for lower extremities including the thigh and gluteal regions. Cutaneous adenolipoma is presumed to be a hamartomatous process. Herein, we report a unique case of a cutaneous eccrine adenolipoma with a spindle cell component, namely, an early evolving spindle cell adenolipoma. Methods: A 43-year-old female with a recurrent history of hidradenitis presented with a 2.7 cm x 1.5 cm x 0.7 cm soft, mobile nodule on the right posterior thigh. It had been present for at least four months and clinically resembled a lipoma. An excisional punch biopsy was performed for pathological evaluation. A concurrent nevus lipomatosus superficialis was diagnosed from the right perineum. Results: Gross examination of the thigh nodule revealed fragments of a tan-yellow, lobulated, fatty lesion. Microscopic examination demonstrated a benign lipomatous proliferation with entrapped eccrine glands associated with a surrounding spindle cell stroma. Initial differential diagnosis included a cutaneous eccrine adenolipoma variant and a cutaneous mixed solitary hamartoma composed of admixed neural, eccrine and lipomatous components. Immunohistochemical staining showed uptake for CD34 and CD10 in the spindle cell stromal component, but negative for desmin and S100. Based on our histopathological findings, our diagnosis of an eccrine cutaneous adenolipoma with a spindle cell component was rendered. This unique lesion displayed features of an evolving spindle cell lipoma with entrapped sweat glands, which may be viewed as an early stage of a dermal spindle cell adenolipoma. Conclusion: Cutaneous eccrine adenolipoma is a rare, benign lipomatous neoplasm with entrapped sweat glands that can also show a spindle cell component. We share this rare lesion exemplifying the histomorphological spectrum of a lipomatous hamartoma and to highlight the recognition of a cutaneous adenolipoma.